Perbaikan Keandalan PLTU Tembilahan dengan Penambahan Kapasitas Pembangkit - Fadhil M Hanafi; Dian Yayan Sukma (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
To ensure good generating system reliability, the presence of operating generating units or adequate power reserves in the generating system is very important. The availability of power reserves in the system depends on various factors, including the frequency of disturbances in generating units and the peak capacity required by the system. One example of a generating system is the Tembilahan steam power plant, which has a capacity of 2 × 7 MW and serves a peak load of 14.31 MW in 2019 until 2022. However, in that period, the reliability of the generating system, as measured by the loss of load expectation (LOLE) index, only reached 33 days/year, far below the standard of the State Electricity Company (Perusahaan Listrik Negara, PT PLN) 2021 to 2030 Electricity Supply Business Plan (Rencana Usaha Penyediaan Tenaga Listrik, RUPTL) of 1 day/year. To improve the reliability of the Tembilahan steam power plant generation system in 2027, an analysis is needed to consider the procurement period of the plant and the availability of land in the system. This analysis involves using the recursive convolution method to calculate the loss of load probability (LOLP)/ loss of load expectation (LOLE) index and the simple linear regression method to estimate the peak load in that year. Based on the results of the analysis, it was found that the addition of three generating units of 7 MW could improve the reliability of the generation system. The area required for these additional units was 2,030.91 m2 and the available land was still sufficient. After the improvements were made, the reliability index LOLE of the generating system increased to 0.078 days/year for the year 2027, meeting the standards for the reliability level of the plant based on PT PLN’s 20212030 RUPTL.